2012
DOI: 10.1016/j.jneumeth.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular diffusion in laminar brain structures exemplified by hippocampus

Abstract: Numerous brain structures are composed of distinct layers and such stratification has a profound effect on extracellular diffusion transport in these structures. We have derived a more general form of diffusion equation incorporating inhomogeneities in both the extracellular volume fraction (α) and diffusion permeability (θ). A numerical solution of this equation for a special case of layered environment was employed to analyze diffusion in the CA1 region of hippocampus where stratum pyramidale occupied by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…Even under normal conditions in rat brain, the CA1 SP has significantly lower ECS volume than the two neighboring layers, stratum oriens (SO) and stratum radiatum (SR; McBain et al, 1990; Saghyan et al, 2012). Saghyan and colleagues (2012) showed that the diffusion of substances across the SP is significantly hindered because of lower ECS volume and lower diffusion permeability in this layer in comparison with adjacent SR and SO.…”
Section: Brain Extracellular Spacementioning
confidence: 99%
See 2 more Smart Citations
“…Even under normal conditions in rat brain, the CA1 SP has significantly lower ECS volume than the two neighboring layers, stratum oriens (SO) and stratum radiatum (SR; McBain et al, 1990; Saghyan et al, 2012). Saghyan and colleagues (2012) showed that the diffusion of substances across the SP is significantly hindered because of lower ECS volume and lower diffusion permeability in this layer in comparison with adjacent SR and SO.…”
Section: Brain Extracellular Spacementioning
confidence: 99%
“…Saghyan and colleagues (2012) showed that the diffusion of substances across the SP is significantly hindered because of lower ECS volume and lower diffusion permeability in this layer in comparison with adjacent SR and SO. To determine the impact of HA deficiency in Has3 KO mice on ECS properties in the CA1 SP, we designed two experiments to study ECS properties in the CA1 region of brain slices taken from Has3 KO mice (Arranz et al, 2014).…”
Section: Brain Extracellular Spacementioning
confidence: 99%
See 1 more Smart Citation
“…During RTI data analysis, the Walter program generates average α and λ , which include the diffusion of all molecules traveling in all axes from a point source to the ISM. If the rate of diffusion is significantly different in any one of the three spatial axes (anisotropy) or if the tissue is non-homogeneous, additional data collection and data analysis are required to calculate α and λ 8,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Larger r distances also minimize brain region-independent differences in the ECS milieu, ISM tip size, and brain tissue damage during ISM placement. Conversely, when r is increased beyond 150 μm, the diffusion of molecules from the iontophoretic point source is more susceptible to influence by non-isotropic, inhomogeneous elements surrounding the brain region of interest or the tissue-perfusate boundary 14 .…”
Section: Discussionmentioning
confidence: 99%